Влияние типа и степени интенсивной пластической деформации на структуру и свойства литых Al—Sc-сплавов - Березина, А.Л.; Монастырская, Т.А.; Давиденко, А.А.; Молебный, О.А.; Полищук, С.С. (Металлофизика и новейшие технологии, 2016)
В сплавах Al—Sc, Al—Sc—Ti, Al—Sc—Ta при интенсивной пластической деформации методами гидроэкструзии и равноканальной угловой гидроэкструзии при комнатной температуре образуются домены с периодической структурой, в которых чередуются области деформированной и недеформированной матрицы с периодом модуляции 0,4—0,7 мкм. Такая структура обусловлена тем, что в процессе накопления деформации при равноканальной угловой гидроэкструзии динамический возврат в сплавах заменяется процессами динамической рекристаллизации с образованием большеугловых границ зёрен размером 0,3—0,8 мкм, соизмеримым с периодом модуляции. У стопах Al—Sc, Al—Sc—Ti, Al—Sc—Ta при інтенсивній пластичній деформації методами гідроекструзії та рівноканальної кутової гідроекструзії за кімнатної температури утворюються домени з періодичною структурою, в яких чергуються області деформованої та недеформованої матриці з періодом модуляції у 0,4—0,7 мкм. Таку структуру зумовлено тим, що в процесі накопичення деформації при рівноканальній кутовій гідроекструзії динамічне повернення у стопах замінюється процесами динамічної рекристалізації з утворенням великокутових меж зерен розміром у 0,3—0,8 мкм, сумірним з періодом модуляції. The effect of monotonous and non-monotonous severe plastic deformations (SPD) on the structure and properties of aluminium alloys is studied. A conventional hydrostatic extrusion (HE) with a constant deformation direction and an equal-channel angular hydroextrusion (ECAH) with an abrupt change in the deformation direction are chosen for the cases of monotonous and nonmonotonous SPD, respectively. Model cast hypoeutectic Al—0.3% Sc alloys and hypereutectic Al—0.6% Sc alloys alloyed with Ta and Ti are chosen in the study. As demonstrated, the SPD of these alloys result in the segregation of the material in active and inactive zones, which form a banded structure. The active zones are shown to be bands of localized plastic deformation. The distance between zones is found to be independent on the degree of accumulated strain and is in the range of 0.6—1 μm. A dynamic recrystallization in the active zones is observed using TEM and is accompanied by the formation of disclinations, deformation bands, low-angle and high-angle boundaries, i.e. rotational deformation modes are developed. A dynamic recrystallization occurs more intensively during the non-monotonous deformation as compared with the monotonous one that is confirmed by the reduction of both stress and texture degree in materials after ECAH.